CAD/CAM TECHNOLOGY IN OPERATIVE DENTISTRY IN THE FIELD OF CONSERVATIVE DENTISTRY - Noor Hafida Widyastuti; Tasha Vella Dianisa (Journal of Health and Dental Sciences, 2026)
The use of Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM) in operative dentistry has been increasingly developed due to the precision, time efficiency, and aesthetic quality of the restorations produced. This study aims to review the latest evidence regarding the application of CAD/CAM in dental conservation. As the use of CAD/CAM in dentistry continues to rise, a systematic review is needed to assess its effectiveness, compare its advantages with conventional methods, and identify its implementation limitations. Secondary data were obtained from Google Scholar, PubMed, and Wiley Online Library. The included articles were peer-reviewed case reports, full-text, published between 2020 and 2025. Older studies (more than 5 years old) were excluded. From an initial 14,138 literature, a systematic selection yielded four articles that met the criteria, involving adult patients with CAD/CAM interventions including post-and-core, lithium disilicate veneer, ZLS onlay, and nano-ceramic onlay for the rehabilitation of worn dentition. The review followed the PRISMA approach, focusing on qualitative synthesis without meta-analysis. All studies demonstrated that CAD/CAM supports more precise, minimally invasive conservative restorations with good marginal adaptation, optimal aesthetics, and time efficiency (single-visit treatment). Modern materials such as ZLS and lithium disilicate yielded satisfactory results at 2 years of follow-up. Patients also reported increased comfort and satisfaction after rehabilitation. The findings are based solely on case reports with small sample sizes and short follow-up periods, thus limiting generalization. CAD/CAM technology shows promise in modern restorative dentistry due to its precision, efficiency, and aesthetics. However, current evidence remains limited, so larger prospective studies with longer follow-ups are necessary. This technology has the potential to become the new standard in dental conservation, supporting digital-based dental education, and encouraging further research on its long-term clinical effectiveness. DOI : 10.54052/jhds.v5n3.p301-310